Plans and disequilibria in centrally planned economies : empirical investigation for Poland - Charemza, Wojciech (Contributions to economic analysis ;, 1988)
The purpose of this study is to investigate interrelations between planning mechanisms and disequilibria in a case where the planning decisions are centralized and are exogenously given to enterprises. The first introductory chapter is intended to provide an understanding of Poland's economic situation during the period under research. In the next five chapters the basic model, describing the households-planners relations in terms of consumption, labour, money and plans are derived, estimated, used for calculation of excess demands, for simulation of some monetary policies, and, finally, for p.